Electrical Energy Audit of Faculty of Technical and Vocational Education (FPTV) of Universiti Tun Hussein Onn Malaysia - Mohamad Yusof, Muhammad Nurnazmi Afiq; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2023)
An electrical energy audit is a thorough analysis of a building’s electrical system to identify inefficiencies and cost-saving opportunities. This paper presents an audit conducted on block C of the FPTV building at UTHM. The objectives of the work include measurements, load profile analysis, energy cost calculations, and proposing Energy Saving Measures (ESMs) based on the findings. The study addresses the issue of excessive electricity consumption at UTHM, compliance with national standards (MS1525:2014). The audit involved a comprehensive assessment, floor drawings, laboratory measurements, illuminance analysis, temperature and humidity evaluation, and data analysis. The study highlights illuminance levels in laboratories and the need for energy-saving measures. The Electrical Technology and Power Supply Labs meet or slightly fall below the recommended illuminance level, while the Building and Surveying Services Lab exceeds it due to natural light. The Micro Teaching Lab significantly surpasses the recommended level with artificial and natural lighting. Maintaining a temperature range of 23°C to 25°C is advised for energy efficiency and user comfort. Humidity levels are generally acceptable, except in the electronic lab where high humidity can cause equipment overheating. The study compares power consumption during physical and online class sessions, showing higher energy usage in physical sessions due to energy-intensive components. Energy-saving measures are categorized as no-cost and mid-cost measures, including behavioral changes, equipment usage reduction, de-lamping, and LED implementation. Implementing the suggested Energy Saving Measures can optimize energy usage, reduce waste, and potentially save money. The research findings contribute to promoting sustainable energy practices in educational institutions, with recommendations for future research to expand the scope and assess specific systems and utilities.